Adaptive Optics Systems VI 2018
DOI: 10.1117/12.2314267
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of lemniscate atmospheric aberrations in Gemini Planet Imager data

Abstract: A semi analytic framework for simulating the effects of atmospheric seeing in Adaptive Optics systems on an 8-m telescope is developed with the intention of understanding the origin of the wind-butterfly, a characteristic twolobed halo in the PSF of AO imaging. Simulations show that errors in the compensated phase on the aperture due to servo-lag have preferential direction orthogonal to the direction of wind propagation which, when Fourier Transformed into the image plane, appear with their characteristic lem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…In addition, by comparing the contribution from the ground layer and the contribution from the jet stream layer for each individual profile, we observe that for about 80% of the profiles, the jet stream layer has a higher contribution to v eff . By correlating the observed WDH direction within high-contrast images from GPI, Madurowicz et al (2018) also showed that the jet stream layer is indeed mainly responsible for the appearance of the WDH in HCI data.…”
Section: Temporal Variation In Atmospheric Turbulencementioning
confidence: 83%
“…In addition, by comparing the contribution from the ground layer and the contribution from the jet stream layer for each individual profile, we observe that for about 80% of the profiles, the jet stream layer has a higher contribution to v eff . By correlating the observed WDH direction within high-contrast images from GPI, Madurowicz et al (2018) also showed that the jet stream layer is indeed mainly responsible for the appearance of the WDH in HCI data.…”
Section: Temporal Variation In Atmospheric Turbulencementioning
confidence: 83%
“…Such time lags are disastrous for exoplanet imaging because they often cause light leakage into the regions closest to the star where planets are most likely to be found (e.g. the "wind butterfly" effect 3,4 ). Predictive WFC is any approach that seeks to compensate for these time lags by predicting the shape of the wavefront one or more time lags into the future based on past wavefront measurements.…”
Section: Introductionmentioning
confidence: 99%
“…This implies different observatory sites with slower winds may have a comparative advantage, as well as the merits in scheduling observations around poor atmospheric conditions. In our previous work [17], we demonstrate that the jet stream is highly correlated with these errors, in a very large sample of observations.…”
Section: Discussionmentioning
confidence: 60%